Nacrt za demokratsku rehabilitaciju Bosne i Hercegovine / Draft For B-H Democratic Rehabiltation - Mujkić, Asim (Pregled: časopis za društvena pitanja / Periodical for social issues, 2018)
This text is a review of a book The State of Bosnia and Herzegovina and Democracy by Prof. Dr. Mirko Pejanović (Sarajevo: University Press, 2017).